Integrasi Kecerdasan Buatan (Artificial Intelligence) dalam Pembelajaran Pendidikan Agama Islam: Peluang, Tantangan, dan Implikasi Pedagogis - Rifa'i Rifa'i; Dania Rahmatillah; Nur Faridah Hidayati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of Artificial Intelligence (AI) technology has brought significant changes to various sectors, including Islamic Religious Education (PAI). This study aims to analyze the opportunities, challenges, and pedagogical implications of AI integration in PAI learning. Using a qualitative approach with library research method, this study examines primary and secondary sources relevant to AI in Islamic education. The results show that AI integration in PAI learning provides opportunities in the form of learning personalization, increased accessibility of religious materials, evaluation efficiency, and development of interactive learning media based on Islamic values. On the other hand, challenges faced include the risk of dehumanization of education, threats to spiritual values, digital gaps, and ethical issues regarding data privacy. The pedagogical implications emphasize the importance of reconstructing the PAI educator paradigm that can integrate digital literacy with spiritual wisdom, so that AI technology serves as a tool, not a substitute, in forming a Muslim generation with noble character and global insight. This study concludes that with proper management, AI has the potential to be an effective supporting tool in creating relevant, adaptive, and Islamic value-based PAI learning.